Determining Best Dressing Factors in Surface Grinding Hardox 500 Using MABAC Technique - Hung, Tran Quoc; Tam, Do Thi; Tung, Luu Anh (European Journal of Applied Sciences, 2024)
This paper presents the results on the application of the multi-criteria decision-making (MCDM) method for selecting the optimal dressing mode for surface grinding of Hardox 500. The study addressed the MCDM problem through the application of the Multi-Attributive Border Approximation Area Comparison (MABAC) method, with criterion weights established via Method Based on the Removal Effects of Criteria (MEREC) method. Additionally, surface roughness (RS) and material removal rate (MRR) were selected as the two criteria for the current study. Also, five dressing variables were analyzed: non-feeding dressing nn, fine dressing depth df, fine dressing times nf, rough dressing depth dr, and rough dressing times nr. Moreover, 16 experimental runs (design’s type L16 (44x21)) were designed and executed. The problem concerning MCDM has been addressed. The investigation’s findings suggest that option No. 5, characterized by the input parameters dr = 0.02 mm, nr = 1, nf = 1, df = 0.01 mm, and nn = 2, represents the optimal dressing mode.